Behavioural Study of Timor Deer (Cervus timorensis) in PT Kuala Tembaga, Aertembaga Village, Bitung-North Sulawesi - Wirdateti, Wirdateti; Mansur, M; Kundarmasno, A (ANIMAL PRODUCTION, 2005)
The objective of this study was to observe the daily behavior of Timor deer (Cervus timorensis). The study was conducted in Aertembaga village, Bitung-North Sulawesi for 30 days. Deer were kept out in the conventional coconut plantations under extensive care system.  Seven Timor deers were used in this study. The daily behavior were observed for their activities; as grazing, ruminating, lying, urinating, defecating, vocalizing, working and other activities. A time sampling method was used to record the behavior activities and observations were repeated in five time.  The respective percentage of daily activities of Timor deer for grazing, ruminating, lying, working, standing,   defecating,  urinating,  approaching  and other activities were 31.17; 14.63; 13.54; 6.23; 7.55; 8.51; 3.96; 7.915 and 6.48%. (Animal Production 7(2): 121-126 (2005) Key Words: Care, Behavior, Timor deer, Extensive